The Influence of Socioeconomic Status on Parental Involvement Among Filipino Parents - Jabar, Melvin (Animo Repository, 2020)
Parental involvement plays a crucial role in the achievement of positive educational outcomes of children. However, the level of involvement among parents varies based on the confluence of individual, familial, and societal factors. Anchored on such premise, this paper aims to investigate the influence of the different socioeconomic related variables to parental involvement, such as monthly income, subjective assessment of living condition, weekly expenditures related to children’s education, and membership in Conditional Cash Transfer (CCT) Program or the Pantawid Pamilyang Pilipino Program (4Ps). It separately analyses parental involvement at home and in school, as these two distinctively involve nuanced practices. This paper is based on a survey conducted with 1,638 parents, mostly experiencing poverty, from 29 public elementary and high schools in six purposively selected municipalities/cities in the Philippines. The survey offers four major findings. First, the parents generally were more or less involved in parental involvement at home than in school. Second, parents in relatively higher income group showed parental involvement both at home and in school. However, a different picture appeared when taking into consideration the subject assessment of parents about their living conditions. Those who considered themselves to be very poor manifested parental involvement at home and in school more than those who viewed themselves to be economically better off. Third, parental involvement in school was relatively higher among CCT member parents than their non-CCT counterparts. Fourth, regression analysis identifies membership in CCT as a predictor of parental involvement. This paper concludes that financial resources from work or the CCT program could facilitate parental involvement in children’s education, especially among parents from relatively high income generating households and families living in poverty. This paper recommends to further examine the impacts of income disparity on parental involvement among parents living in poverty. Most studies look at variations in parental involvement across income groups. However, even within a specific income group, levels of parental involvement thus vary. Hence, it is interesting to know if intra-group income differentials can explain and predict variations in levels of parental involvement among families in the lowest income quantile of the population.